Mahmud Yunus' Book of 'Ilmu Mushthalah al-Hadith: Existence, Typology, and Uniqueness in Indonesian Hadith Studies - Gusnanda Gusnanda; Hanifatul Husna (Jawahir Al-Ahadis, 2025)
This paper describes the book 'Ilmu Mushthalah al Hadith written by Mahmud Yunus. This study specifically looks at three main aspects, namely the existence, systematic writing, and analysis of the contents of the book. The findings of the study reveal that at present the book of hadith science written by Mahmud Yunus is not widely used by madrasas and universities. The most basic reason is because the book is written in a simple and incomplete form. Regarding the writing systematics, it is slightly different from other books of 'Ulum al-Hadis. The book consists of 96 pages and about 73 topics. Unfortunately, this book does not contain all topics related to 'Ulum al-Hadith. This book only contains a few topics, and mostly explains terms related to 'Ulum al-Hadith. One interesting point about this book is that Mahmud Yunus has created a special chapter entitled Criticism of Sahihain and Criticism of Ibn Salah's words.